Footprints in the sand: What can globular clusters tell us about NGC 4753 past? - Caso, Juan Pablo (2015)
NGC 4753 is a bright (Mv~-22.3) lenticular galaxy. It is a very interesting target to test different theories of formation of lenticular galaxies, due to its low-density environment and complex structure. We perform the first comprehensive study of NGC4753 globular cluster system (GCS), using Gemini/GMOS and CTIO/MosaicII images. Our results indicate a rather poor GCS of ~1000 members. Its azimuthal distribution follows the shape of the galaxy bulge. The GC colour distribution is peculiar, presenting an intermediate subpopulation in addition to blue and red ones. This intermediate subgroup can be explained by a single stellar population with an age of 1.53 Gyr and 0.5 − 1 Zo. The GC specific frequency Sn = 1.3 +/- 0.15 is surprisingly low for a galaxy of its class. The GC luminosity function (GCLF) is also peculiar, with an excess of bright GCs compared to the expected gaussian distribution. The underlying galaxy body has significant substructure, with remnants of spiral arms, dust filaments, and isophote twisting. This, and the fact that NGC4753 hosted two type Ia SNe, support the possibility that the intermediate GC subpopulation may have originated during a recent merger, 1-3 Gyr ago.